Missed Proximal Tracheoesophageal Fistula (TEF) in a Neonate with Type D Esophageal Atresia - Menso, Julia E.; Reijntjes, Maud A.; Oomen, Matthijs W.; Rinkel, Rico N.P.M.; Terheggen-Lagro, Suzanne W.J.; Gorter, Ramon R. (European Journal of Pediatric Surgery Reports, 2024)
We present the case of a patient with the rare type D esophageal atresia (EA), diagnosed after correction of an EA initially diagnosed as type C. Routine postoperative contrast esophagogram showed a missed proximal tracheoesophageal fistula. This case report illustrates the potential difficulties to diagnose type D EA.
Keywords: esophageal atresia; type D; tracheoesophageal fistula; diagnosis